COVID-19 vaccination intention: The combined role of pathogen disgust and trust in government - Peng, Shun; Chen, Jiwen; Xu, Lei (Frontiers in Psychology, 2023)
The present study aimed to investigate the joint effect of pathogen disgust and trust in government on COVID-19 vaccination intention and to examine the mediating role of COVID-19 worry. A total of 2,244 participants were recruited to participate in the study. The results indicated the following: (1) Individuals' COVID-19 vaccination intention was significantly higher when "congruence was high" than when "congruence was low", given comparable levels of pathogen disgust and trust in government. (2) There were no significant differences in individual COVID-19 vaccination intention with incongruence levels of pathogen disgust and trust in government. (3) The combination of pathogen disgust and trust in government can influence COVID-19 vaccination intention through COVID-19 worry. This study sought to gain a new perspective on how pathogen disgust might contribute to COVID-19 vaccination intention.